PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Febransyah Febransyah; Titi Suelmi (Universitas Tridinanti, 2021)
This study aims to obtain empirical evidence about: (1) Effect of Capital Structure on Financial Performance (2) Effect of Liquidity on Financial Performance. The population of this research is all banking companies listed on the Indonesia Stock Exchange in 2014-2018 amounting to 25 companies. The sampling technique is purposive sampling. The sample of this research is 125 companies. Data analysis with multiple regression.The results of this study concluded that: (1) Capital Structure and Liquidity did not significantly influence Financial Performance (2) Capital Structure partially had a significant effect on Financial Performance (3) Liquidity partially had no significant effect on Financial Performance. In this research it is recommended to conduct further studies by including other independent variables that are suspected to have an influence on financial performance so that the scope is wider and more references to other researchers. Keywords: Capital Structure, Liquidity, Financial Performance